Genome-wide association analysis of feed intake and residual feed intake in Nellore cattle - Santana, Miguel H. A.; Utsunomiya, Yuri T. [UNESP]; Neves, Haroldo H. R. [UNESP]; Gomes, Rodrigo C.; Garcia, José Fernando [UNESP]; Fukumasu, Heidge; Silva, Saulo L.; Oliveira Junior, Gerson A.; Alexandre, Pamela A.; Leme, Paulo R.; Brassaloti, Ricardo A.; Coutinho, Luiz L.; et al. (Biomed Central Ltd., 2014)
Background: Feed intake plays an important economic role in beef cattle, and is related with feed efficiency, weight gain and carcass traits. However, the phenotypes collected for dry matter intake and feed efficiency are scarce when compared with other measures such as weight gain and carcass traits. The use of genomic information can improve the power of inference of studies on these measures, identifying genomic regions that affect these phenotypes. This work performed the genome-wide association study (GWAS) for dry matter intake (DMI) and residual feed intake (RFI) of 720 Nellore cattle (Bos taurus indicus).Results: In general, no genomic region extremely associated with both phenotypic traits was observed, as expected for the variables that have their regulation controlled by many genes. Three SNPs surpassed the threshold for the Bonferroni multiple test for DMI and two SNPs for RFI. These markers are located on chromosomes 4, 8, 14 and 21 in regions near genes regulating appetite and ion transport and close to important QTL as previously reported to RFI and DMI, thus corroborating the literature that points these two processes as important in the physiological regulation of intake and feed efficiency.Conclusions: This study showed the first GWAS of DMI to identify genomic regions associated with feed intake and efficiency in Nellore cattle. Some genes and QTLs previously described for DMI and RFI, in other subspecies (Bos taurus taurus), that influences these phenotypes are confirmed in this study.